Xanthomonas oryzae pv. oryzae BAKTERI PENYEBAB HAWAR DAUN PADA PADI: ISOLASI, KARAKTERISASI, DAN TELAAH MUTAGENESIS DENGAN TRANSPOSON - Wahyudi, Aris Tri; Meliah, Siti; Nawangsih, Abdjad Asih (UI Scholars Hub, 2011)
Xanthomonas oryzae pv oryzae the Causal Agent of Bacterial Leaf Blight of rice: Isolation, Characterization, and Study of Transposon Mutagenesis. X. oryzae pv. oryzae (Xoo) causes bacterial leaf blight (BLB) of rice (Oryza sativa L.), a major disease that constrains production of the staple crop in many countries of the world. Identification of X. oryzae pv. oryzae (Xoo) was conducted based on the disease symptoms, pathogenicity, morphological, physiological, and genetic characteristics of bacterial cultures isolated from the infected plants. Fifty bacterial isolates predicted as Xoo have been successfully isolated. They are aerobic, rod shaped, and Gram negative bacteria. The isolates were evaluated for their hypersensitivity in tobacco and pathogenicity in rice plant. Fifty isolates induced hypersensitive reaction in tobacco and showed pathogenicity symptom in rice in different length. Based on physiological test, hypersensitivity and pathogenicity reactions, three bacterial isolates strongly predicted as Xoo, i.e. STG21, STG42, and STG46, were non indole formation, non pigment fluorescent, hydrolyzed casein, catalase activity positive, but negative oxidase. Partial sequencing of 16S rRNA genes of STG21 and STG42 showed 80% and 82% homology with X. oryzae, respectively, while STG46 showed 84% homology with X. campestris. Mini-Tn5 transposon mutagenesis of STG21 generated one of the mutants (M5) lossed it’s ability to induce hypersensitive reaction in tobacco plant and deficient in pathogenicity on rice. The lesion length of rice leaf caused by the mutant M5 decreased up to 80%.